PROFITABILITY OF THE TAMBAN SALAI FISH PROCESSING BUSINESS IN SINGKEP PESISIR DISTRICT LINGGA REGENCY - Anisa, Nur; Tetty, Tetty; Hafsar, Khairul (Politeknik Kelautan dan Perikanan Dumai, 2024)
Singkep Pesisir sub-district in Lingga Regency is home to six beautiful villages, including Berindat, Kote, Lanjut, Pelakak, Persing, and Sedamai. The local residents are primarily fishermen, and the area is well-known for the Tamban Salai fish processing business. This business is committed to providing high-quality fish products and is a significant contributor to the local economy. Our research aimed to determine the income and profitability of the Tamban Salai Fish Processing business in Singkep Pesisir district. We used a quantitative descriptive method and collected data through a census method. The financial analysis included Benefit Cost Of Ratio (B/C Ratio), Revenue Cost Of Ratio (R/C Ratio), Break-Even Point (BEP Unit), Break-Even Point (BEP Rupiah), Return On Equity (ROE), and Return On Investment (ROI) to measure the feasibility and profitability of the business. Our research found that the Tamban Salai Fish Processing business is a highly feasible and profitable business with a B/C Ratio of 4.00, R/C Ratio of 5.00, BEP Unit of 1,211.62 kg, and BEP Rupiah of Rp10,787.91. The Return On Equity (ROE) was 84%, and Return On Investment (ROI) was 35%. At the Tamban Salai Fish Processing business, we believe in delivering the best quality products to our customers while contributing to the local economy. Our commitment to excellence has allowed us to establish ourselves as a trustworthy and reliable business. We are proud of our success and look forward to continuing to serve our customers with the same dedication and commitment.